The Legal Review Regarding Copyright Protection of Songs from Unauthorized Song Cover Actions - Rachmat Satyo Krismanto; Luluk Lusiati Cahyarini (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The copyright infringement is an act prohibited by the law, in practice copyright infringement is divided into several forms of song piracy in Indonesia which results in losses from the creator and the state, therefore the government tries to enforce copyright law. Problems in writing this scientific paper are related to forms of violations, arrangements and legal protection efforts for the rights of songwriters in Indonesia. This research uses a normative juridical approach. Meanwhile, the conclusion of this study is that an activity does not include copyright infringement as long as the acts and covers related to the song's artwork are noncommercial and the creator also gets benefits without objection to the activity. On the other hand, we also need to know that there are a lot of Indonesians who cover and upload it on social media in the form of Youtube, Instagram and Tiktok. Article 43 and Article 44 of the Copyright Act explain the criteria for whether the activity meets the elements of copyright infringement or not. As for legal protection efforts, one of them is by preventing (preventive) and cracking down (repressive). One way is by socializing with the community. Although of course the government has also taken many related actions, with maximum results. But for us, it is not the wrong thing to remind each other about copyright infringement.